2019
DOI: 10.2147/ppa.s219346
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence Of Potentially Inappropriate Medication In The Older Adult Population Within Primary Care In Portugal: A Nationwide Cross-Sectional Study</p>

Abstract: BackgroundIn potentially inappropriate medications harm potentially outweighs benefits. Even appropriately prescribed medications may become inappropriate. They can lead to a high risk of adverse drug reactions, morbidity and mortality. The aim of this study was to determine the prevalence of potentially inappropriate medication in the older adult population attending primary care in Portugal and to identify associated sociodemographic and clinical factors.MethodsWe conducted a cross-sectional, analytical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 28 publications
8
50
1
7
Order By: Relevance
“…In the Northeast, Midwest and South of Brazil, the prevalence was lower, 21.6% [ 16 ], 26.0% [ 8 ], and 42.4% [ 2 ], respectively. International studies have shown prevalence rates of 43% in Canada [ 15 ], 42,7% in New Zealand [ 11 ], and 46.1% in Portugal [ 41 ]. In Asian countries, the prevalence was 12.7% in Oman [ 42 ], 34.0% in India [ 43 ], 39.4% in Indonesia [ 44 ], 53,1% in Kuwait [ 14 ], and 59.3% in Thailand [ 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the Northeast, Midwest and South of Brazil, the prevalence was lower, 21.6% [ 16 ], 26.0% [ 8 ], and 42.4% [ 2 ], respectively. International studies have shown prevalence rates of 43% in Canada [ 15 ], 42,7% in New Zealand [ 11 ], and 46.1% in Portugal [ 41 ]. In Asian countries, the prevalence was 12.7% in Oman [ 42 ], 34.0% in India [ 43 ], 39.4% in Indonesia [ 44 ], 53,1% in Kuwait [ 14 ], and 59.3% in Thailand [ 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Lithuania, a similar study performed on almost half a million subjects revealed that the prevalence of PIM use ranged from 24.1 to 57.2% depending on criteria used to defined PIM (79). In a more recent national survey in Portugal looking at PIM in 705 older patients followed in primary care, a potentially inappropriate medication was present in 68.6 and 46.1% of the sample had two or more (80). The impact of PIM in older as well as in younger patients is multiple.…”
Section: Inappropriate Drug Prescribing and Adherence In Elderlymentioning
confidence: 95%
“…This is the case for example of non-steroidal anti-inflammatory drugs (NSAIDs), which are known to increase blood pressure and to blunt the antihypertensive efficacy of diuretics or blockers of the renin-angiotensin system. In the Portuguese survey, NSAIDs belong to the top three PIM identified in elderly patients (80). Moreover, studies have suggested that PIM increases morbidity and mortality and health care costs in elderly (79,81,82).…”
Section: Inappropriate Drug Prescribing and Adherence In Elderlymentioning
confidence: 99%
“…The results related to the PIMs have already been published [13], but they are not necessarily related to the polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to identify the nationwide prevalence of polypharmacy in older adults in Portugal and its sociodemographic and clinical profiles. Although polypharmacy can be linked to drug-drug interactions (both pharmacokinetics and pharmacodynamics) and to adverse drug reactions, these results were presented in a previous paper [13]. Moreover, given the lack of consensus for the definition of polypharmacy and since multimorbidity and the use of multiple medications is common in older adults [14] we also intended to use a new definition of polypharmacy (equal to or greater than the median number of drugs taken by the population) and compare it to the most commonly used.…”
Section: Introductionmentioning
confidence: 89%